A Checklist of the Lycidae (Coleoptera) of Colombia with a key to the genera - Daniela Moreno; Elynton Alves do Nascimento; Dimitri Forero (Caldasia)
A checklist of the genera and species of Lycidae occurring in Colombia is presented. After studying nine Colombian entomological collections, in addition to the information from the literature, 152 species and 27 genera are recorded from the country, of which four genera are newly recorded from Colombia: Brasilycus, Ceratopriomorphus, Lycoplateros, and Teroplas. The genus Calopteron presented the widest distribution (29 departments), the only genus occurring in Arauca, Córdoba, La Guajira, and Vaupés. Most genera in Colombia occur from lowland habitats (~500 m) up to 2000 m, whereas Idiop-teron Bourgeois, 1905, showed the widest altitudinal range, from about 30 m to 3900 m. An illustrated key to identify the Colombian genera is provided.